Tumor Budding in Upper Gastrointestinal Carcinomas - Koelzer, Viktor H.; Langer, Rupert; Zlobec, Inti; Lugli, Alessandro (Frontiers in Oncology, 2014)
The basis of personalized medicine in oncology is the prediction of an individual’s risk of relapse and death from disease. The presence of tumor budding (TB) at the tumor-host interface of gastrointestinal cancers has been recognized as a hallmark of unfavorable disease biology. TB is defined as the presence of dedifferentiated cells or small clusters of up to five cells at the tumor invasive front and can be observed in aggressive carcinomas of the esophagus, stomach, pancreas, ampulla, colon and rectum. Presence of TB reproducibly correlates with advanced tumor stage, frequent lymphovascular invasion, nodal and distant metastasis. The UICC has officially recognized TB as additional independent prognostic factor in cancers of the colon and rectum. Recent studies have also characterized TB as a promising prognostic indicator for clinical management of esophageal squamous cell carcinoma, adenocarcinoma of the gastro-esophageal junction and gastric adenocarcinoma. However, several important issues have to be addressed for application in daily diagnostic practice: 1) Validation of prognostic scoring systems for tumor budding in large, multi-center studies 2) Consensus on the optimal assessment method 3) Inter-observer reproducibility. This review provides a comprehensive analysis of TB in cancers of the upper gastrointestinal tract including critical appraisal of perspectives for further study.